2019
DOI: 10.5812/compreped.89804
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Exclusive Breastfeeding in 6 Month-Old Infants: A Population-Based Case-Control Study

Abstract: Background: Exclusive breastfeeding contributes to the health and survival of the newborn. Many factors influence this behavior. Objectives: This study aimed to identify the related determinant factors. Methods: In this case-control study 8130 cases that did not have exclusive breastfeeding at 6 months of age were matched with 53266 people from control group. The two groups were compared in terms of risk factors such as sex, birth rank, weight, height and head circumference, type of delivery, maternal age, hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
1
1
1
Order By: Relevance
“…This study, which found no correlation between breastfeeding and children's cognitive abilities, differs markedly from much of the existing literature showing positive effects (15,16). There are some possible reasons for this discrepancy, such as the timing of the study (most studies show effects occurring later, such as at school-going age).…”
Section: Discussioncontrasting
confidence: 98%
“…This study, which found no correlation between breastfeeding and children's cognitive abilities, differs markedly from much of the existing literature showing positive effects (15,16). There are some possible reasons for this discrepancy, such as the timing of the study (most studies show effects occurring later, such as at school-going age).…”
Section: Discussioncontrasting
confidence: 98%
“…In addition, to the mother who work usually only has a period of maternity leave or short maternity leave, so that the period of exclusive breastfeeding is not achieved because job demands that require mothers to return to work. The main cause for failure and formula initiation was themother's return to work (Aghaee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A amamentação exclusiva até os 6 meses de idade e complementada com alimentos saudáveis até os 2 anos ou mais é altamente defendida. O AME é sabidamente benéfico para o binômio mãe-bebê, protege os bebês contra todas as formas de desnutrição, além de proteger as mães contra doenças, como diabetes e câncer de mama 3 .…”
Section: Introductionunclassified